The Role of National Saving in the World Economy : Recent Trends and Prospects: Occa Paper No.67. (Occasional Papers; Occasional Paper ;, 1990)
This paper reviews and analyzes broad developments and considers specific policy measures to foster saving. The chapter also describes trends in national saving rates of industrial countries in recent years and briefly discusses the prospects over the medium term. The paper also discusses the effects of policy measures on national saving and investment. Fiscal, monetary, and exchange rate policies are all shown to have major implications for saving in developing countries. Fiscal restraint is especially important, since it increases national saving by both raising public saving and reducing the country's dependence on foreign borrowing. Exchange rate devaluation and the unification of exchange markets also appear to be effective in stimulating national saving. Interest rates and financial reforms play a crucial role in effecting an efficient allocation of resources, including the mobilization of savings to finance domestic investment.